Diversity, mechanisms and beneficial features of phosphate-solubilizing Streptomyces in sustainable agriculture: A review - Chouyia, Fatima Ezzahra; Ventorino, Valeria; Pepe, Olimpia (Frontiers in Plant Science, 2022)
Currently, the use of phosphate (P) biofertilizers among many bio-formulations attracted a large interest for sustainable agriculture. Streptomyces genus could display positive interaction with plant by acting as growth promoters. Several studies have shown the great potential of this bacterial group in supplementing P in plant soluble form by several mechanisms. Furthermore, some of P solubilizing Streptomyces (PSS) are known as plant growth promoting rhizobacteria able to promote plants through other features, as increasing the availability of soil nutrients, producing wide range of antibiotics, phytohormones, bioactive compounds, and secondary metabolites other than antimicrobials. Thereby, the use of PSS with multiple plant growth promoting activities as alternative strategies appears to limit the negative impacts of the chemical fertilizers in agriculture practices on the environmental and human health as well as to explore their potential effect to enhance plant fitness and crop yield. In spite, studies on Streptomyces as P solubilizers still insufficient and unclear comparing to studies on other gram-positive bacteria. Although PSS were reported as potential bio-inoculant both in greenhouses and field experiments, but until now no PSS-based biofertilizers being commercialized. In this regard, this review emphasizes an overview mainly of the P solubilization activity by Streptomyces including their use as P biofertilizers in competitive agronomic practices, their mechanisms to release P by solubilization/mineralization, for increasing both P efficiency in soil and plant growth. It further highlights and discusses the beneficial association of PSS with plant in detail with latest development and research to expand the horizon of field application as P biofertilizers by exploiting their numerous advantages in improving crop production to fulfill the world food demand.